2020
DOI: 10.1021/acs.macromol.0c01909
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Hydration of Asymmetric Polyelectrolyte Multilayers as Studied by Neutron Reflectometry: Connecting Multilayer Structure to Superior Membrane Performance

Abstract: Porous membranes coated with so-called asymmetric polyelectrolyte multilayers (PEMs) have recently been shown to outperform commercial membranes for micropollutant removal. They consist of open support layers of poly­(styrene sulfonate) (PSS)/poly­(allylamine) (PAH) capped by denser and more selective layers of either PAH/poly­(acrylic acid) (PAA) or PAH/Nafion. Unfortunately, the structure of these asymmetric PEMs, and thus their superior membrane performance, is poorly understood. In this work, neutron refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…For the asymmetric system, these characterization methods suggest rather distinct layers of PAH/PAA and PAH/ PSS, which has been indicated in the literature. 59 While zeta potential is dominated by the top layer of PAH/PAA (2 bilayers), the overall swelling behavior of the film is dominated by PAH/PSS (8 bilayers), due to the higher relative layer number. Direct Membrane Characterization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the asymmetric system, these characterization methods suggest rather distinct layers of PAH/PAA and PAH/ PSS, which has been indicated in the literature. 59 While zeta potential is dominated by the top layer of PAH/PAA (2 bilayers), the overall swelling behavior of the film is dominated by PAH/PSS (8 bilayers), due to the higher relative layer number. Direct Membrane Characterization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We mainly attribute the minor increase in swelling compared to the pure PAH/PAA system to the dominant amount of PAH/PSS layers (8 bilayers). While it was shown that these kind of asymmetric films indeed form rather distinct layers, 59 slight intermixing of the systems could influence the overall swelling degree.…”
Section: Resultsmentioning
confidence: 99%
“…As a solvent with a high dielectric constant (78.36 F m −1 , 25 °C), water tends to enhance the screening of charges along the main chains of polyelectrolytes and thus increase the possibility of splitting the electrostatic interaction between positively charged groups on polycation and negatively charged groups on polyanion. [ 44–46 ] With the existence of the screening effect, the polarity of both the NH 3 + groups and the COO − groups within a PEI/PAA‐N 3 film is expected to be attenuated under water. This can be verified by the shift of the vibrating peaks of NH 3 + groups and COO − groups to higher wavenumbers on the attenuated total reflectance Fourier transform infrared (ATR‐FTIR) spectra of a wet (PEI/PAA‐5.4N 3 ) 10 film, compared to that of a dry one (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…In another work, neutron reflectometry (NR) was used to distinguish the support and separation layers of membranes composed of polyelectrolyte multilayers. 24 NR reveals that the membranes have an asymmetric structure with distinct bottom and top multilayers in either the dried or hydrated state. It has also been demonstrated that reduced hydration leads to denser and consequently more selective separation layers.…”
Section: Freeman Et Al Developed a New And Simple Methods To Determin...mentioning
confidence: 99%
“…It is revealed that on the nanometer length scale water diffuses through the desalination membrane at a rate similar to bulk water, while water diffuses through the AEM 2 times slower than bulk water. In another work, neutron reflectometry (NR) was used to distinguish the support and separation layers of membranes composed of polyelectrolyte multilayers . NR reveals that the membranes have an asymmetric structure with distinct bottom and top multilayers in either the dried or hydrated state.…”
mentioning
confidence: 99%